Developing a Change Management and Leadership Strategy for Delivering successful transformational change: A case study of Adult Social Care - Williams, Lisa (2016)
I have researched the most effective way to deliver successful transformational change, particularly focusing on developing a change management and leadership strategy for delivering successful transformational change in an adult social care environment. Adult Social care is currently facing substantial challenges, with the increase in demand for the demographic group, with many older people not getting the care and support they need (Humphries et al, 2016). The Care Act 2014 has introduced new rights and responsibilities (Hansard, 2015), against a backdrop of reduced funding, with authorities current savings at 3% every year (Bolton, 2016). Both in the public and private sector organisations are struggling to deliver effective transformational change, with in excess of seventy per cent of change efforts failed or where they were achieved, did not meet the original cost, quality or time parameters of the change programme (Kotter, 1996). The case study aims to focus research on the most significant theories established in the literature review, which are Kotter’s (1995) “eight step process” framework for delivering change and the alignment theory presented by Collins & Porras (1998) and Duck (1998). I intend to use these theories to analyse the case study, test the theories in a practical business environment and determine how useful they are in delivering transformational change. I plan to make recommendations on the main findings of the case study: • The critical element to delivering change is creating alignment (Collins & Porras, 1998) and to use the theory described by Duck (1998) to implement this in practice, alongside the “eight step process” (Kotter, 1995). • Ensure the sequencing of the “eight step process” (Kotter, 1995) is followed as this is a crucial part of delivering change successfully. • Create a true sense of urgency (Kotter, 2008) • Further develop leadership capabilities (Kotter, 2001, Goleman, 2000) The key finding from the research is that the vision is the merely the mechanism for bringing the vision to life, it is creating alignment which is the critical element to delivering change (Collins & Porras, 1998). The key recommendation from the research, as a contribution to a further understanding of theories examined in the case study and as a potential area for further research is: • The optimum way to deliver successful change management is to use Kotter’s (1995) “eight step process” alongside the theory of alignment (Collins & Porras, 1998).